Modular Approaches to Cyclopentanoids and their Heteroanalogs - Kotha, Sambasivarao; Tangella, Yellaiah (Synlett, 2020)
Cyclopentanoids and their derivatives are interesting targets in synthetic organic chemistry due to their extensive applications in various branches of chemical sciences like pharmaceuticals, natural and non-natural products. In view of these applications, several synthetic strategies have been developed in the past three to four decades. In this article, we describe our work towards the synthesis of cyclopentanoids and their heteroanalogs involving diverse synthetic strategies during the past two decades. Among these, photo-thermal olefin metathesis, ring-closing metathesis, ring-rearrangement metathesis, cyclopentane annulation, [2+2+2] cycloaddition and Diels–Alder reactions have been used to assemble cyclopentane rings of diverse architecture. 1 Introduction 2 Synthesis of Spiro[4.4]nonane (A1) Derivatives 3 Synthesis of Octahydropentalene (A2) Derivatives 4 Synthesis of Linear Triquinanes (A3) 5 Synthesis Spiro Triquinanes (A4) 6 Synthesis of Angular Triquinane (A5) Systems 7 Synthesis of Hexahydro-2′H-spiro[cyclopentane-1,1′-pentalene] (A6) Ring System 8 Synthesis of Dispiro[4.1.47.25]tridecane (A7) Ring System 9 Synthesis of Hexahydro-1H-3a,7a-propanoindene Ring System10 Synthesis of Linear Tetraquinanes (A11 and A12)11 Synthesis of Tetrahydro-1′H,3′H-dispiro[cyclopentane-1,2′-pentalene-5′,1′′-cyclopentane] (A13) Ring System12 Synthesis of Decahydro-1H,8H-dicyclopenta[a,h]pentalene (A14) Ring System13 Synthesis of Dodecahydro-1H-dicyclopenta[a,d]pentalene (A15) Ring System14 Synthesis of Octahydro-1′H-spiro[cyclopentane-1,2′-cyclopenta[c]pentalene] (A16) Ring System15 Synthesis of Decahydrospiro[cyclopentane-1,7′-cyclopenta-[a]pentalene] (A17) Ring System16 Synthesis of Compact Tetraquinane (A18)17 Synthesis of Higher Polyquinanes18 Conclusions19 Acronyms
Keywords: cyclopentanoids; metathesis; cycloaddition; allylation; Grignard reaction; Fischer indolization; Claisen rearrangement